Partial Purification of Dipeptidyl Peptidase-4 From Human Blood Serum and Study the Inhibitory Effect of Some Nitrile Derivatives on it - Firas Shawqi Algburi; Nadia Y Al-Tikrity; Hasan Ulusal; Tugba Taskin-Tok (Indian Journal of Forensic Medicine & Toxicology, 2021)
The research includes the partial purification of dipeptidyl peptidase-4(Dpp-4) from a person’s natural serum.The enzyme was purified in three steps, precipitation by ammonium sulfate (50%), dialysis and gel filtration by Sephadex G-100. The results showed a significant increase of Dpp-4 activity and specific activity,and a decrease in total activity after purification.The descent of the purified enzyme with the highest activity from the separation column was identical to the descending of the protein with the highest activity. The inhibitory activity of nitrile derivatives that were used on the purified enzyme was studied. Nitrile derivatives were used to inhibit the activity of the Dpp-4, selected based on similarity in sites of effective groups between derivatives and anti-hyperglycemic drugs (Dpp-4 inhibitors type). The results show an inhibitory effect by the two nitrile derivatives with different concentrations.These inhibitors can work to reduce the level of blood sugar in people with diabetes. Moreover,Molecular docking was exerted to understand interaction mechanism of the compounds against Dpp-4 at atomic level based on experimental processes.